Drosophila Mutant Model of Parkinson's Disease Revealed an Unexpected Olfactory Performance: Morphofunctional Evidences. (28th August 2016) - De Rose, Francescaelena; Corda, Valentina; Solari, Paolo; Sacchetti, Patrizia; Belcari, Antonio; Poddighe, Simone; Kasture, Sanjay; Solla, Paolo; Marrosu, Francesco; Liscia, Anna
Abstract : Parkinson's disease (PD) is one of the most common neurodegenerative diseases characterized by the clinical triad: tremor, akinesia, and rigidity. Several studies have suggested that PD patients show disturbances in olfaction as one of the earliest, nonspecific nonmotor symptoms of disease onset. We sought to use the fruit fly Drosophila melanogaster as a model organism to explore olfactory function in LRRK loss-of-function mutants, which was previously demonstrated to be a useful model for PD. Surprisingly, our results showed that the LRRK mutant, compared to the wild flies, presents a dramatic increase in the amplitude of the electroantennogram responses and this is coupled with a higher number of olfactory sensilla. In spite of the above reported results, the behavioural response to olfactory stimuli in mutant flies is impaired compared to that obtained in wild type flies. Thus, behaviour modifications and morphofunctional changes in the olfaction of LRRK loss-of-function mutants might be used as an index to explore the progression of parkinsonism in this specific model, also with the aim of studying and developing new treatments.